2007
DOI: 10.1063/1.2794010
|View full text |Cite
|
Sign up to set email alerts
|

Large-area, ordered hexagonal arrays of nanoscale holes or dots from block copolymer templates

Abstract: Hexagonal arrays of nanoscale holes or metal dots (25nm in diameter and 39nm in period), with orientational order extending over the entire square-centimeter array area, were fabricated on unpatterned silicon wafer substrates using a shear-aligned sphere-forming diblock copolymer template. Since two or more layers of spherical nanodomains are required to achieve alignment in the block copolymer film, but pattern transfer requires a single layer, a multistep etching process was developed, whereby the top layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…Shearing of these films was performed as previously described, 11,12 well above the glass transition temperature of both blocks, in a glove box under nitrogen atmosphere. 18 For transmitting the shear stress to the film, PDMS pads (1 cm  1 cm) were prepared by curing a mixture of Dow Corning Sylgard 184/curing agent (15/1 w/w) at 60 C for 4 h. While holding the specimen at a constant temperature ranging from 140-170 C via a digital hot plate, shear stresses of 5-20 kPa were applied for min. The specimen was then cooled to below the PS matrix glass transition temperature (ca.…”
Section: Methodsmentioning
confidence: 99%
“…Shearing of these films was performed as previously described, 11,12 well above the glass transition temperature of both blocks, in a glove box under nitrogen atmosphere. 18 For transmitting the shear stress to the film, PDMS pads (1 cm  1 cm) were prepared by curing a mixture of Dow Corning Sylgard 184/curing agent (15/1 w/w) at 60 C for 4 h. While holding the specimen at a constant temperature ranging from 140-170 C via a digital hot plate, shear stresses of 5-20 kPa were applied for min. The specimen was then cooled to below the PS matrix glass transition temperature (ca.…”
Section: Methodsmentioning
confidence: 99%
“…[151] However, it was found that a monolayer of PEP spheres cannot be shear aligned due to a lack of mechanical anisotropy in hexagonal lattices, and hence two or more layers of spheres were required to obtain good lateral ordering of shear-aligned spherical microdomains. [152][153][154][155] It was also demonstrated that the presence of defects, like dislocations, is an intrinsic limitation of this technique. However, it is advantageous over other methods described in Sections 3.1 and 3.2, as predefined patterns are not required, and the process is simple and easily applicable to larger areas.…”
Section: Engineering Approachesmentioning
confidence: 96%
“…[11,12] Hexagonal arrays of dots can be formed either from a sphere forming BCP or from vertically oriented cylinders. [13,14] Whereas line arrays can be formed from cylinders oriented parallel or lamellas oriented vertically to the substrate. [15,16] The later is advantageous for pattern transfer due to the connectivity between the substrate and the film surface and the ability to fabricate high aspect ratio features.…”
mentioning
confidence: 99%